Impact and Outcomes of a Pediatric Robotic Urology Mini-Fellowship - Andolfi, Ciro; Patel, Dev; Rodriguez, Veronica M.; Gundeti, Mohan S. (Frontiers in Surgery, 2019)
Introduction: In order to support practicing pediatric surgeons and urologists to safely incorporate robotic surgery into their practice, we established a 5-day Pediatric Robotic Mini-Fellowship (PRM) program. This study was designed to report our experience and to evaluate the impact this course had on the participants’ practice. Methods: The PRM training at our institution is provided in two modules, including upper and lower urinary tract surgery, over a five-day period. The one to one teacher-to-attendee experience included tutorial sessions, hands-on inanimate and animate skills training, clinical case observations and video discussions. Participants were asked to complete a detailed questionnaire on their practice patterns before and after the PRM. Results: Between 2012 and 2018, a total of 29 national and international pediatric surgeons and urologists underwent robotic renal and bladder surgery training. Twenty-six fellows (90%) completed the surveys, all of which were included for analysis. The median age at the time of fellowship was 43 years (32-63), and participants had practiced urology for a median of 76 months (3-372). All of them had a laparoscopic background. The most common primary goals of participants were to understand the concept of robotic surgery and its applications and to practice in the wet lab to shorten their learning curve. After PRM completion, 24 graduates (92%) felt likely to incorporate robotic surgery into their practice, of which 15 (58%) actually started a robotic program at their home institution. At 24 months after PRM completion, the overall number of surgeries performed with a robotic approach (RA) by these 15 MF participants was 478 with an average of 32 procedures per fellow, of which 109 (23%) were extirpative and 369 (77%) reconstructive procedures. These data mark a significant switch in indications for minimally invasive pediatric urology, with a rise in the number of reconstructive procedures performed in a minimally invasive fashion. Conclusion: A five-day intensive PRM appears to enable postgraduate surgeons to successfully incorporate the robotic platform into their practice and to advance the complexity of minimally invasive procedures, allowing for more challenging surgeries, such as reconstructive urology.